Teachers’ Utilization and Challenges of ICT-Enabled Inquiry in Physics Education - Renalyn V. Perez; Marc Paul T. Calzada; Rhea M. Cabrera (Future Science / FSH-PH Publications, 2026)
Information and Communication Technology (ICT) has become increasingly important in science education, particularly in supporting Inquiry-Based Learning (IBL) in physics, where learners often encounter difficulties in understanding abstract concepts. This study examined the ICT tools utilized by junior high school physics teachers and the challenges they encountered in implementing inquiry-based learning in the Schools Division of Ilocos Norte, Philippines (SDOIN).The study employed a descriptive-quantitative research design with qualitative support. Using non-probability purposive sampling, 126 junior high school physics teachers from selected public schools participated in the study, while 25 teachers were interviewed to provide qualitative insights. Data were collected using a researcher-developed survey questionnaire and an expert-validated semi-structured interview guide. Frequency counts and percentages were used to describe the participants' profiles, while mean and ranking were employed to analyze ICT utilization. Qualitative responses were analyzed using thematic analysis.The findings showed that the most used ICT tools were those that were easily accessible such as multimedia presentation with the use of projector, digital camera or mobile phone, and virtual laboratory or simulation. But the overall use of ICT in inquiry-based learning was found to be moderate. The thematic analysis showed that the use of ICT in inquiry was hindered by time constraints, lack of resources and infrastructural capacity, low readiness of the learners for inquiry, diversity and participation of learners, and communication.